THE IMPACT OF PROPRIOCEPTIVE NEUROMUSCULAR FACILITATION AND DYNAMIC STRETCHING ON LOWER LIMB FLEXIBILITY IMPROVEMENT: A SYSTEMATIC REVIEW - I Fadhilah; Yanuar Kiram; Padli (RADJA PUBLIKA, 2026)
A systematic review is therefore needed to consolidate existing evidence and identify the dominant factors This systematic review was conducted to consolidate evidence on how proprioceptive neuromuscular facilitation (PNF) and dynamic stretching affect hamstring flexibility. Literature searches were carried out using the Scopus database. Two empirical studies up to the year 2025 were analyzed from an initial pool of 113 findings, including interventions combining PNF and dynamic/ballistic stretching. Thematic analysis focused on two main dimensions: the effectiveness of stretching techniques in improving hamstring flexibility and the acute impact of stretching on explosive performance. The synthesis results indicate that both dynamic stretching (including ballistic stretching) and PNF can improve hamstring flexibility in structured interventions, making them effective for reducing muscle stiffness and expanding the range of motion. In pre-activity contexts, dynamic or ballistic stretching tends to enhance neuromuscular readiness and supports the ability to generate power immediately after warm-up, making it suitable before activities that require high power output. Conversely, certain PNF variations ending with passive static stretching were found to decrease acute explosive performance despite improving muscle looseness, making them less appropriate as part of competitive warm-ups. Overall, this review emphasizes that the selection of stretching techniques should consider two primary goals: whether the priority is to improve hamstring flexibility or to maintain and even optimize explosive performance immediately after warm-up